A study on the relationship between compensation gap within the top management team and corporate performance: An empirical research based on the moderation effect of fairness preference - Wang, Xi; Chen, Xue; Zhou, Haoqian; You, Xiangbo (Frontiers in Psychology, 2022)
This study explores the relationship between the compensation gap within the top management team(TMT) and corporate performance. We focus on how the fairness preference of the TMT moderates this relationship. The existing researches on the relationship between the compensation gap within the TMT and corporate performance is inconclusive. The reason may be that the traditional tournament theory is based on the hypothesis of self-interest preference of homo oeconomicus. In the research, the fairness preference theory is added to the traditional tournament model, and a more realistic tournament model considering fairness preference is constructed. Based on the analysis of the theoretical model and the empirical regression analysis of the panel data of 733 non-financial A-share listed companies in Shanghai and Shenzhen stock markets from 2014 to 2020, we draw the following main conclusions: (1)There is an inverted U-shaped relationship between the TMT compensation gap and the corporate performance. Within the optimal compensation gap, there is a significant positive correlation. The larger the compensation gap, the better the corporate performance will be. When the optimal compensation gap is exceeded, there is a significant negative correlation. The larger the compensation gap, the worse the corporate performance will be. (2) The fairness preference of the TMT will weaken the correlation between the TMT compensation gap and corporate performance. Within the optimal compensation gap, the fairness preference will weaken the positive relationship between them, and when it exceeds the optimal compensation gap, the fairness preference will also weaken the negative relationship between them.